Science has no sex : the life of Marie Zakrzewska, M.D. - Tuchman, Arleen, 1956- (Studies in social medicine., 2006)
German-born Marie Zakrzewska (1829@-1902) was one of the most prominent female physicians of nineteenth-century America. Best known for creating a modern hospital and medical education program for women, Zakrzewska battled against the gendering of science and the restrictive definitions of her sex. In ###Science Has No Sex#, Arleen Tuchman examines the life and work of a woman who continues to challenge historians of gender to this day.